Acrocallosal Syndrome in a 6-Month-Old Pakistani Infant - Rifayatullah Afridi; Aneela Ambreen; Faizan Ali Janjua (Gandhara University, 2016)
Acrocallosal syndrome is a rare autosomal recessive disorder. The prevalence of the disease is not known but fewer than 55 cases have been published since 1979. ACS is characterized by the total or partial absence of the corpus callosum, Minor craniofacial anomalies (prominent forehead, hypertelorism, short nose with anteverted nostrils and large anterior fontanel) moderate to severe psychomotor retardation (with hypotonia), polydactyly or polysyndactyly. We are reporting a case of 6 month old infant child who was admitted to the hospital with pneumonia, measles, episodes of fits, large anterior fontanelle, prominent forehead, high arched palate, fused tongue, micrognathism , hypotonia, motor developmental delay , polysyndactyly and absent corpus callosum. His clinical diagnosis was confirmed by CT-Brain. The patient was managed for superimposed pneumonia and measles. He was provided with other supportive treatment as well as parental counseling, physiotherapy sessions, and multiple disciplinary approaches was undertaken for further management.